Sedimentary recycling in Jianchuan Basin, SE Tibetan Plateau: A solution to the debate on the formation age of the First Bend (Yangtze River) - Zhang, Zengjie; Daly, J. Stephen; Tian, Yuntao; Wang, Yuejun; Badenszki, Eszter; Sun, Xilin; Liu, Yimin (Geomorphology (Amsterdam, Netherlands), 2023)
The sedimentary archive of the Jianchuan Basin provides a critical constraint on the formation of the “First Bend”, a major geomorphological feature of the Yangtze River, involving an abrupt 150° change in flow direction. Despite extensive detrital zircon provenance studies, no consensus has been reached on the timing of this event. Prior to the formation of the First Bend, the Yangtze is thought to have flowed southwards through the Jinchuan Basin, entering the South China Sea via the Red River. In this study, we constrain the timing of the First Bend using detrital K-feldspar Pb isotopic and detrital zircon U-Pb age datasets from Jianchuan Basin sandstones. Provenance data from late Eocene detrital zircon and K-feldspar populations concur in suggesting that they were fed by the southward flowing paleo-upper Yangtze River. Distinct K-Feldspar Pb isotopic data indicate that the overlying later Eocene and Pliocene deposits were fed by local Eocene syenites, granites and tuffs. Stratigraphic constraints on this change in provenance indicate that the southward flowing paleo-Yangtze River was cut off in the late Eocene at or before ∼37 Ma, thereby dating the formation of the First Bend. In contrast, detrital zircon U-Pb geochronology from the youngest units within the Jianchuan Basin is similar to those of the older sandstones and upper Yangtze River sands. This evidence indicates that the majority of zircons deposited in the upper part of the Jianchuan Basin were recycled from older sedimentary rocks. In our view, much of the disagreement relating to the formation time of the First Bend can be attributed to the failure to recognize sedimentary recycling. This study highlights the need to consider the possible presence of recycled detrital zircons when investigating paleo-drainage systems.